Semantic facilitation and translation priming effects in Chinese-English bilinguals - Chen, Hsuan-Chih; Ng, Man-Lai (Memory & cognition, 1989)
In two experiments, semantic facilitation and translation priming effects in Chinese-English bilingual speakers were demonstrated with a lexical decision task. A 300-msec stimulus-onset asynchrony (SOA) was used between display of the prime and the target item. Experiment 1 showed that subjects' lexical decision responses were facilitated to a greater extent when primed by a translation equivalent than a semantically related between-language word. In Experiment 2, we found that pictorial, between-language, and within-language primes produced comparable effects of semantic facilitation. These results are in line with the hypothesis that lexical items in different languages and pictures are processed by means of an amodal conceptual system.